The Aquatic Metatron: A large‐scale experimental facility to study the combined effects of habitat fragmentation and climate change on aquatic meta‐ecosystems - Murielle Richard; Alexandre Garreau; Elvire Bestion; Julien Cucherousset; Jose M. Montoya; Simon Blanchet (Methods in Ecology and Evolution)
Abstract Revealing the effects of multiple global change drivers on ecosystem dynamics and functioning is a crucial endeavour, which necessitates the use of appropriate tools. Here, we present the Aquatic Metatron, a unique mesocosm facility providing a large‐scale experimental resource to study the combined effects of global change components, in particular climate change and habitat fragmentation, on the ecological and evolutionary dynamics of aquatic ecosystems. The Aquatic Metatron consists of 144 mesocosms of 2 m3 each that can be connected to each other with aquatic corridors, and—for a subset of them—with aerial corridors. This enables effective control of dispersal across meta‐ecosystems. In addition, the temperature in each mesocosm is supervised and precisely controlled, either through a heating (all mesocosms) or a cooling (72 mesocosms) system. All mesocosms can be monitored automatically for abiotic and biotic factors (pH, dissolved oxygen, conductivity, turbidity and chlorophyll a) allowing for long‐term experimentation. We tested the platform by conducting three experiments involving the manipulation of various components of global change: climate warming, biodiversity loss, eutrophication and aquatic/aerial fragmentation. The technical innovations of the platform have been validated, in particular its capacity to accurately recreate multiple climatic scenarios (e.g. heatwaves, warming, cooling) and the possibility of using aerial and water corridors to simulate fragmented landscapes. The Aquatic Metatron is located in the south‐west of France (https://sete‐moulis‐cnrs.fr/fr) and is part of AnaEE France and AnaEE‐ERIC (https://www.anaee.eu/), which are large‐scale research infrastructures. The Aquatic Metatron is a research facility accessible to external researchers and projects.